Anne Byrd - (:unkn) unknown (Z. Smith Reynolds Library, 1979)
ca. 1970
Alumna Anne Byrd, cooking in kitchen; photo appeared in Wake Forest Magazine Spring 1979, p. 15
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth